R&D on the gas injection system of Beam Induced Fluorescence Monitor toward MW beam power at the J-PARC Neutrino Beam-line. (February 2020) - Nakamura, A.; Koshio, Y.; Friend, M.; Sakashita, K.
Abstract: A Beam Induced Fluorescence (BIF) monitor is being developed as an essential part of the monitor update toward MW beam power operation at the J-PARC neutrino beam line, where a 30 GeV proton beam is extracted, bent and struck onto a 90-cm-long graphite target to produce an intense and nearly pure muon (anti-)neutrino beam for the Tokai-to-Kamioka(T2K) experiment. A BIF monitor can measure the proton beam profile non-destructively and continuously spill-by-spill with fluorescence light produced by proton- N 2 interactions. In order to generate enough light to measure the profile precisely, it is necessary to temporarily increase the vacuum pressure near the BIF interaction point up to ~ 10 −2 Pa during each beam spill while keeping the average pressure low (10 −4 to 10 −6 Pa) at other locations to protect vacuum equipment. Therefore, R&D of a pulsed gas injection system satisfying these requirements is in progress. We will report the recent R&D status of the gas injection system and prospects toward operation of a prototype monitor which we plan to install this fall 2019.